An improved dual-polarized ratio algorithm for sea ice concentration retrieval from passive microwave satellite data and inter-comparison with ASI, ABA and NT2 - Zhang, Shugang; Zhao, Jinping; Li, Min; Liu, Shixuan; Zhang, Shuwei (Journal of oceanology and limnology, 2018)
The dual-polarized ratio algorithm (DPR) for the retrieval of Arctic sea ice concentration from Advanced Microwave Scanning Radiometer-EOS (AMSR-E) data was improved using a contrast ratio (CR) parameter. In contrast to three other algorithms (Artist Sea Ice algorithm, ASI; NASA-Team 2 algorithm, NT2; and AMSR-E Bootstrap algorithm, ABA), this algorithm does not use a series of tie-points or a priori values of brightness temperature of sea-ice constituents, such as open water and 100% sea ice. Instead, it is based on a ratio ( α ) of horizontally and vertically polarized sea ice emissivity at 36.5 GHz, which can be automatically determined by the CR. α exhibited a clear seasonal cycle: changing slowly during winter, rapidly at other times, and reaching a minimum during summer. The DPR was improved using a seasonal α . The systematic differences in the Arctic sea ice area over the complete AMSR-E period (2002–2011) were -0.8%±2.0% between the improved DPR and ASI; -1.3%±1.7% between the improved DPR and ABA; and -0.7%±1.9% between the improved DPR and NT2. The improved DPR and ASI (or ABA) had small seasonal differences. The seasonal differences between the improved DPR and NT2 decreased, except in summer. The improved DPR identified extremely low ice concentration regions in the Pacific sector of the central Arctic (north of 83°N) around August 12, 2010, which was confirmed by the Chinese National Arctic Research Expedition. A series of high-resolution MODIS images (250 m×250 m) of the Beaufort Sea during summer were used to assess the four algorithms. According to mean bias and standard deviations, the improved DPR algorithm performed equally well with the other three sea ice concentration algorithms. The improved DPR can provide reasonable sea ice concentration data, especially during summer.